Synthesis of nanosized LiNbO3 photonic crystals for optical waveguides - Fakhri, Makram Abdulmuttaleb (Institute of Nano Electronic Engineering, 2016)
The aim of the study is to synthesize, analyze and characterize LiNbO3 photonic thin films on quartz using sol-gel and spray pyrolysis method for optical strip waveguide applications. The study is accomplished by the following by the following specific objectives to investigate nano and micro size of LiNbO3 photonic crystal properties on selected substrates; to compare nanophotonic crystal of LiNbO3 films using different approches; to charactrize LiNbO3 crystals using different techniques; to design and fabricate optical strip shape waveguide.